Stock Parts Availability Improvement, Case: Wärtsilä Finland Oy, Services - Köykkä, Minna (My University, 2008)
Successful inventory management is a challenging part of managing the overall business. Determining the correct level of inventory is quite hard, especially in the spare part businesses. Availability can establish competitive advantage for companies, if they can offer products at promised time for their customers. The goal of this study is to research how the availability can be improved by inventory control. In the beginning of this study the materials management is generally researched. For this study the most interesting activities under materials management are forecasting, stock parts control and availability. In the stock parts control it is concentrated especially in safety stock and reorder point calculation. In this study the usability of stock control tool in Wärtsilä Finland Oy, Services is determined. The main problem is that the availability is too low and the stock value is too high. The used stock control tool is AIM-program, by which it hasn’t been reached the desired availability. The purpose is to find out how the stock parts should be controlled so that the availability target can be reached. The research method is a constructive approach, which has been carried out based on the literary and the practical knowledge of inventory control at Wärtsilä Services. The research result is that better availability can be reached, when AIM-program is not used. Nowadays stock control is done by SAP and with the help of a separate planning tool. With these tools and some improvements in SAP material master the adjust target of the availability has been achieved. As literature of this research has been used inventory management books, researches on stock control tool and scientific publications.
Keywords: Inventory control; Availability; fi=Tuotantotalous|en=Industrial Management|